Aviation Heritage in the Urban Landscape—Concept and Examples from Berlin - Edyta Pijet-Migoń (Heritage, 2025)
Aviation heritage, though relatively recent in historical terms, constitutes an important and increasingly recognized component of urban cultural landscapes. This article explores how former airports and aviation-related infrastructure have been preserved, adapted, or commemorated in Berlin—a city with a uniquely complex aviation history shaped by political division, technological progress, and evolving urban needs. Based on a typology proposed by the author, the study analyzes five former airport sites in Berlin (Johannisthal, Staaken, Tempelhof, Gatow, and Tegel), employing historical research, field observations, and spatial analysis. The results reveal a wide spectrum of approaches to aviation heritage, ranging from complete erasure to creative reuse integrating ecological, recreational, educational, and symbolic functions. The study also highlights the role of aviation heritage in fostering local identity and contributing to sustainable tourism. The proposed typology may serve as a useful tool for assessing and managing aviation heritage in other urban contexts.